Plasma Dynamics in Low-Electron-Beta Environments - Boldyrev, Stanislav; Loureiro, Nuno F.; Roytershteyn, Vadim (Frontiers in Astronomy and Space Sciences, 2021)
Recent in situ measurements by the MMS and Parker Solar Probe missions bring interest to small-scale plasma dynamics (waves, turbulence, magnetic reconnection) in regions where the electron thermal energy is smaller than the magnetic one. Examples of such regions are the Earth's mangetosheath and the vicinity of the solar corona, and they are also encountered in other astrophysical systems. In this brief review, we consider simple physical models describing plasma dynamics in such low-electron-beta regimes, discuss their conservations laws and their limits of applicability.